3D Hydrazone‐Functionalized Covalent Organic Frameworks as pH‐Triggered Rotary Switches. Issue 41 (12th September 2021) - Zhao, Wenjuan; Yu, Chengyang; Zhao, Jie; Chen, Fengqian; Guan, Xinyu; Li, Hui; Tang, Bin; Yu, Guangtao; Valtchev, Valentin; Yan, Yushan; Qiu, Shilun; Fang, Qianrong
Abstract: The property expansion of 3D functionalized covalent organic frameworks (COFs) is important for developing their potential applications. Herein, the first case of 3D hydrazone‐decorated COFs as pH‐triggered molecular switches is reported, and their application in the stimuli‐responsive drug delivery system is explored. These functionalized COFs with hydrazone groups on the channel walls are obtained via a multi‐component bottom–up synthesis strategy. They exhibit a reversible E / Z isomerization at various pH values, confirmed by UV–vis absorption spectroscopy and proton conduction. Remarkably, after loading cytarabine (Ara‐C) as a model drug molecule, these pH‐responsive COFs show an excellent and intelligent sustained‐release effect with an almost fourfold increase in the Ara‐C release at pH = 4.8 than at pH = 7.4, which will effectively improve drug‐targeting. Thus, these results open a way toward designing 3D stimuli‐responsive functionalized COF materials and promote their potential application as drug carriers in the field of disease treatment. Abstract : 3D hydrazone‐decorated covalent organic frameworks as pH‐triggered molecular switches are obtained via a multi‐component bottom–up synthesis strategy, and are used for the stimuli‐responsive drug delivery system.